2004
DOI: 10.1890/03-0043
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Characterizations Underestimate the Role of Edaphic Factors Controlling the Distribution of Entandrophragma

Abstract: Numerous theories have been developed and tested to explain the high botanical diversity in tropical forests, ranging from nonequilibrium theories emphasizing the importance of chance to equilibrium theories depicting highly specialized species occupying narrow ecological niches. Niche-based theories have most often evaluated species adaptation to different light environments, but some studies have evaluated the importance of edaphic attributes in controlling species distributions. We evaluated the role of eda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
87
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 42 publications
3
87
0
3
Order By: Relevance
“…Seedlings of these species have been shown experimentally to develop best in approximately 25% full sunlight (Synnott, 1975;Pieters, 1976;Swaine et al, 1997;Agyeman et al, 1999;Hall et al, 2003c). Hall et al (2004) linked adult meso-scale spatial distribution patterns of three of these four Entandrophragma spp. (E. angolense, E. candollei, and E. cylindricum) to edaphic factors and suggested that growth performance helps explain adult tree distribution of E. candollei and E. cylindricum seedlings in relation to soil fertility (Hall et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings of these species have been shown experimentally to develop best in approximately 25% full sunlight (Synnott, 1975;Pieters, 1976;Swaine et al, 1997;Agyeman et al, 1999;Hall et al, 2003c). Hall et al (2004) linked adult meso-scale spatial distribution patterns of three of these four Entandrophragma spp. (E. angolense, E. candollei, and E. cylindricum) to edaphic factors and suggested that growth performance helps explain adult tree distribution of E. candollei and E. cylindricum seedlings in relation to soil fertility (Hall et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…(Carroll, 1997); mean temperature varies between 24 8C (December) and 29 8C (April). Soils within the study area are generally classed as oxisols but with important variability in fertility within the study site (see Hall et al (2004) for further description).…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of edaphic factors in maintaining local diversity has long been recognized (29,30), a thorough, quantitative assessment of the importance of soil resources on tropical tree distributions for entire communities has not been undertaken. Typically, studies have either focused on a small fraction of the tree species in any community (31)(32)(33) or related community-wide tree species distributions to topographical variables whose relationships with underlying soil resources are unknown (28,34,35). To test relationships between species distributions and soil resource availability, soil resources and species distributions need to be mapped at high spatial resolution for entire communities in plots large enough to span substantial spatial heterogeneity in soil factors.…”
mentioning
confidence: 99%
“…Shorea, Polyalthia and Aporosa in S.E. Asia, Ashton 1988;Rogstad 1990;Debski et al 2002; Entandrophragma in the Central African Republic, Hall et al 2004; Rinorea in Ecuador, Valencia et al 2004).…”
Section: Introductionmentioning
confidence: 99%